2002
DOI: 10.1034/j.1600-0773.2002.900310.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for the Study of Factors Affecting Angiogenesis

Abstract: Experimental evidence has accumulated over the years to show that a variety of strategies that limit neovascularisation also slows down or inhibits tumour growth, suggesting that blocking tumour-induced angiogenesis is a valid, novel approach to tumour therapy (Folkmann 1997).The rat Subcutaneous Air Sac (SAS) model (Lichtenberg et al. 1997(Lichtenberg et al. & 1999 was recently described as a new in vivo model designed to replace a currently used eye model where neovascularisation is induced by chemical injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…One of these demonstrated a proangiogenic effect of ifosfamide in xenotransplanted breast cancer, 22 whereas the other study showed a decrease of vessel density in a nontumoral model of angiogenesis. 23 Antitumoral mechanisms such as antiproliferative effects and activation of lymphocyte infiltration did not seem to be involved 3 weeks after the start of therapy. It is possible that these parameters were affected at the earlier phase; however, this aspect was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One of these demonstrated a proangiogenic effect of ifosfamide in xenotransplanted breast cancer, 22 whereas the other study showed a decrease of vessel density in a nontumoral model of angiogenesis. 23 Antitumoral mechanisms such as antiproliferative effects and activation of lymphocyte infiltration did not seem to be involved 3 weeks after the start of therapy. It is possible that these parameters were affected at the earlier phase; however, this aspect was not investigated in our study.…”
Section: Discussionmentioning
confidence: 99%